The Significance of Tumor Necrosis Factor Receptor Type II in CD8+ Regulatory T Cells and CD8+ Effector T Cells - Ye, Lin-Lin; Wei, Xiao-Shan; Zhang, Min; Niu, Yi-Ran; Zhou, Qiong (Frontiers in Immunology, 2018)
Tumor necrosis factor (TNF) is a pleiotropic cytokine that has both pro-inflammatory and anti-inflammatory functions. The biological functions of TNF are mediated by two receptors, TNF receptor type I (TNFR1) and TNF receptor type II (TNFR2). TNFR1 is expressed universally on almost all cell types and has been extensively studied, whereas TNFR2 is mainly restricted to immune cells and some tumor cells and its role is far from clarified. Studies have shown that TNFR2 mediates the stimulatory activity of TNF on CD4+Foxp3+regulatory T cells (Tregs) and CD8+Foxp3+Tregs, and is involved in the phenotypic stability, proliferation, activation, and suppressive activity of Tregs. TNFR2 can also be expressed on CD8+effector T cells(Teffs), which delivers an activation signal and cytotoxic ability to CD8+Teffs during the early immune response, as well as an apoptosis signal to terminate the immune response. TNFR2-induced abolition of TNF receptor-associated factor 2 (TRAF2) degradation may play an important role in these processes. Consequently, due to the distribution of TNFR2 and its pleiotropic effects, TNFR2 appears to be critical to keeping the balance between Tregs and Teffs, and may be an efficient therapeutic target for tumor and autoimmune diseases. In this review, we summarize the biological functions of TNFR2 expressed on CD8+Foxp3+Tregs and CD8+Teffs, and highlight how TNF uses TNFR2 to coordinate the complex events that ultimately lead to efficient CD8+T cell-mediated immune responses.